Diabetic neuropathy differs between type 1 and type 2 diabetes: insights from magnetic resonance neurography - Jende, Johann; Gröner, Jan; Oikonomou, Dimitrios; Heiland, Sabine; Kopf, Stefan; Pham, Mirko; Nawroth, Peter Paul; Bendszus, Martin; Kurz, Felix T. (Annals of neurology, 2018)
Objective To visualize and quantify differences of microstructural nerve damage in distal symmetric diabetic neuropathy (DPN) between type 1 diabetes (T1D) and type 2 diabetes (T2D), and to detect correlations between neuropathic symptoms and serological risk factors. Methods Three-tesla magnetic resonance neurography of the sciatic nerve was performed in 120 patients (T1D, n = 35; T2D, n = 85) with either DPN (n = 84) or no DPN (n = 36). Results were subsequently correlated with clinical, serological, and electrophysiological patient data. Results T2-weighted (T2w)-hyperintense lesions correlated negatively with tibial compound motor action potential (r = −0.58, p < 0.0001) and peroneal nerve conduction (r = 0.51, p = 0.0002), and positively with neuropathy disability score (NDS; r = −0.54, p < 0.0001), neuropathy symptom score (NSS; r = 0.52, p < 0.0001), and HbA1c level (r = 0.23, p = 0.014). T2w-hypointense lesions correlated positively with NDS (r = 0.28, p = 0.002), NSS (r = 0.36, p < 0.0001), and serum triglycerides (r = 0.34, p = 0.0003), and negatively with serum high-density lipoprotein (HDL; r = −0.48, p < 0.0001). For DPN in T1D, elevated values of T2w-hyperintense lesions (19.67 ± 4.13% vs 12.49 ± 1.23%, p = 0.027) and HbA1c (8.74 ± 0.29% vs 7.11 ± 0.16%, p < 0.0001) were found when compared to T2D. For DPN in T2D, elevated T2w-hypointense lesions (23.41 ± 2.69mm3 vs 11.43 ± 1.74mm3, p = 0.046) and triglycerides (220.70 ± 23.70mg/dl vs 106.60 ± 14.51mg/dl, p < 0.0001), and lower serum HDL (51.29 ± 3.02mg/dl vs 70.79 ± 4.65mg/dl, p < 0.0001) were found when compared to T1D. Interpretation The predominant type of nerve lesion in DPN differs between T1D and T2D. Correlations found between lesion type and serological parameters indicate that predominant nerve lesions in T1D are associated with poor glycemic control and loss of nerve conduction, whereas predominant lesions in T2D are associated with changes in lipid metabolism. These findings may be helpful for future studies on the underlying pathophysiological pathways and possible treatments for DPN in T1D and T2D. Ann Neurol 2018;83:588-598
Gesehen am 03.03.2020